The Effect of Antecedents on Online Streaming Subscription on Vidio Companies - Tania Jovita Wibowo; Martinus Tjhia Tjen Jong (Jurnal Mantik, 2021)
As the time goes by and by the developing technologies, there are much shifting conditions because of that development, including in the media industry. Technologies bring ease and options. The increasing options may bring factors that can influence customers in choosing whether to use cable TV or an online streaming platform for their entertainment. Based on research by Lee et al (2018), there are factors which can affect customer decision about choosing cable TV or online streaming platform. Those factors are ease of use, additional purchases, media options, social trends, available options, and cost.